RHEUMATIC FEVER: SEMICENTENNIAL EXPERIENCE IN STUDYING THE PROBLEM. REFLECTIONS OF A RHEUMATOLOGIST - N. N. Kuzmina; L. G. Medyntseva; B. S. Belov (Научно-практическая ревматология)
The paper presents the main milestones of a long-term study of the time course of acute rheumatic fever (ARF) in a Russian contingent of patients from different age groups, the results of studying of the clinical types of the disease, developing, and introducing methods for its diagnosis, treatment, rehabilitation and prevention programs. It highlights a path of successes and disappointments in the control of ARF, the way in which every answer is followed by a new question.